Rancang Bangun Model Strategi Operasional Implementasi Lean Manufacturing Berkesinambungan Untuk Peningkatan Produktivitas Industri Pengolahan Kayu di Indonesia - Aminudin Soetara; Machfud Machfud; M. Joko Affandi; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2019)
The purposes of this research were to identify factors affecting the success and failure in implementing the continuous lean manufacturing (LM) of woodworking industry in Indonesia. This research applied Soft System Methodology (SSM) to construct PAM conceptual model (Purposeful Activity Model) through continuous implementations of Lean Manufacturing (LM) in Indonesia’s woodworking industry. The Purposeful Activity Model (PAM) has been compared with real world and verified by experts, practitioners and academicians. The results of Analytical Hierarchy Process (AHP) had determined the important roles of owners, and middle and top management. The commitment of middle and top management is required for the continuous implementation of Lean Manufacturing. The main strategic program includes employees’ lean basic training on its concept, philosophy, culture and basic techniques; in addition, the implementation of Lean Manufacturing should be in sequence to provide strong foundation to assure LM continuation. The results of Strategic Assumption Surfacing and Testing (SAST) indicated that there are 5 strategic assumptions which are required to assure successful LM implementation; i.e. the company’s maturity and readiness on lean foundation, supports from owners and executives to implement LM, harmonious working environment, the company’s good financial health condition, and being in an industrial environment running an excellent and proper Lean Manufacturing activities and systems.Keywords: AHP, lean culture, lean manufacturing, SAST, SSMAbstrak: Tujuan penelitian ini adalah mengidentifikasi faktor-faktor yang menyebabkan kegagalan dan keberhasilan dalam implementasi lean manufacturing (LM) yang berkesinambungan pada industri pengolahan kayu di Indonesia. Studi ini menerapkan SSM (Soft System Methodology) yang menghasilkan model konseptual PAM (Purposeful Activity Model) implementasi LM berkesinambungan di industri perkayuan Indonesia. Model konseptual PAM telah dilakukan pembandingan dengan dunia nyata dan verifikasi dengan pakar, praktisi dan akademisi. Hasil AHP (Analytical Hierarchy Process) menunjukkan pemilik, manajemen puncak dan menengah sebagai aktor utama yang berperan, serta komitmen manajemen puncak dan menengah menjadi faktor utama yang berpengaruh dalam implementasi LM berkesinambungan. Strategi utama, yaitu (1) memberikan pelatihan kepada seluruh karyawan untuk mengikuti pelatihan dasar lean, konsep dan filosofi lean, budaya lean, dan teknik-teknik dasar LM serta (2) penerapan LM dasar secara bertahap sebagai pondasi yang kuat agar implementasi LM berjalan secara berkesinambungan. Berdasarkan hasil SAST (Strategic Assumption Surfacing and Testing) terdapat lima asumsi startegik sebagai prasyarat keberhasilan implementasi LM, yaitu Perusahaan telah memiliki tingkat kematangan atau kesiapan pondasi lean; Adanya dukungan pemilik perusahaan untuk mengimplementasikan LM; Kondisi kerja yang harmonis; Kondisi perusahaan yang sehat dari aspek finansial; Berada di lingkungan industri yang telah menjalankan excellent manufacturing atau sistem manufaktur yang baik dan benar.Kata kunci: AHP, lean culture, lean manufacturing, SAST, SSM